The Religiosity, Nationality, and Sociality of Pancasila: Toward Pancasila through Soekarno’s Way - Latif, Yudi (Studia Islamika, 2018)
Pancasila is the five principles of the Indonesian state’s philosophical foundation. Its existence reflects the characteristics of Indonesia as a multicultural nation-state, one which has to absorb and transform all elements of the nation into a strong, permanent foundation, and a dynamic guiding principle. The five principles are viewed as the crystalisation of the core values and ideals of the nation, as idealised by the existing “trilogy ideology”: religious ideologies, nationalist ideologies and socialist ideologies. All of the ideologies had been synthesized in order to find a common ground that realises the common good (al-maṣlaḥah al-‘āmmah) for the life of the nation. The history of the conceptualisation of Pancasila had been a long process featuring the “seeding” phase, “formulation” phase, and “commencement” phase. Each phase involves the participation of various actors and elements. However, in a joint work of the nation, one of the most prominent actors is Soekarno. To understand Pancasila, one needs to understand his life and thoughts.DOI: 10.15408/sdi.v25i2.7502